Remotely sensed hydroacoustics and observation data for predicting fish habitat suitability - Monk, J.; Ierodiaconou, D.; Bellgrove, A.; Harvey, Euan; Laurenson, L. (Elsevier Ltd, 2011)
This paper investigates the use of using remotely sensed observation and full coverage hydroacoustic datasets to quantify habitat suitability for a marine demersal fish, the blue-throated wrasse. Because of issues surrounding the detection of species using remotely sensed video techniques, the application of presence-only techniques are well suited for modeling demersal fish habitat suitability. Ecological-Niche Factor Analysis is used to compare analyses conducted using seafloor variables derived from hydroacoustics at three spatial scales; fine (56.25 m2), medium (506.25 m2) and coarse (2756.25 m2), to determine which spatial scale was most influential in predicting blue-throated wrasse habitat suitability. The coarse scale model was found to have the best predictive capabilities with a Boyce Index of 0.80±0.26. The global marginality and specialization values indicated that, irrespective of spatial scale, blue-throated wrasse prefer seafloor characteristics that are different to the mean available within the study site, but exhibit a relatively wide niche. Although variable importance varied over the three spatial scale models, blue-throated wrasse showed a strong preference for regions of shallow water, close to reef, with high rugosity and maximum curvature and low HSI-B values. Generally the spatial patterns in habitat suitability were well represented in the Marine National Park compared to adjacent waters. However, some significant differences in spatial patterns were observed. Interspersion and Juxtaposition Indexes for unsuitable and highly suitable habitat were significantly smaller inside the Marine National Park, while the Mean Shape Index of unsuitable habitat in the Marine National Park was significantly larger.